Night of the Long Knives - Tolstoy, Nikolai (New York Ballantine Books, 1972)
One of Adolf Hitler's most brutal and dramatic exterminations came before the Holocaust. The SA was Hitler's army of thugs, but the head of the SA, Ernst Roehm, was threatening Hitler's rule. On June 29th 1934, Hitler ordered the SA leadership to appear for a meeting at the Hotel Hanselbauer. Without warning, the SS burst in, beginning 48 hours of bloodshed in which 1000 of the leading SA, including Roehm, were rounded up and slaughtered. This murderous deed became an omen of what was to come
Include Illustration
Keywords: Hitler, Adolf, 1889-1945 -- Germany -- Politics and government